2016
DOI: 10.2460/javma.249.2.165
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Shelter Veterinarians’ 2016 Veterinary Medical Care Guidelines for Spay-Neuter Programs

Abstract: As community efforts to reduce the overpopulation and euthanasia of unwanted and unowned cats and dogs have increased, many veterinarians have increasingly focused their clinical efforts on the provision of spay-neuter services. Because of the wide range of geographic and demographic needs, a wide variety of spay-neuter programs have been developed to increase delivery of services to targeted populations of animals, including stationary and mobile clinics, MASHstyle operations, shelter services, community cat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 199 publications
0
26
0
Order By: Relevance
“…There is a misconception that small cats may be harassed by other adult cats and that they may require a longer recovery time after undergoing surgery. However, the surgical procedures for young adult cats are easier, faster, and safer than the procedures used for older cats (Kustritz, 2007;Bushby & Griffin, 2011;Porters et al, 2014;Griffin et al, 2016). Indeed, probability of disease (mammary hyperplasia, ovarian cysts, and increased friability and vascularity of the uterus) in younger female cats is lower than in older female cats, and postoperative recovery is faster in younger cats than in older cats (Yates & White, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There is a misconception that small cats may be harassed by other adult cats and that they may require a longer recovery time after undergoing surgery. However, the surgical procedures for young adult cats are easier, faster, and safer than the procedures used for older cats (Kustritz, 2007;Bushby & Griffin, 2011;Porters et al, 2014;Griffin et al, 2016). Indeed, probability of disease (mammary hyperplasia, ovarian cysts, and increased friability and vascularity of the uterus) in younger female cats is lower than in older female cats, and postoperative recovery is faster in younger cats than in older cats (Yates & White, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…4,[147][148][149] Analysis of the current literature reveals that there is minimal risk for surgical complications or subsequent developmental abnormalities between pediatric gonadectomy performed on dogs between 6 and 14 weeks of age and gonadectomy performed on dogs at the more traditional age of 6 months, both of which are prior to puberty. 3,4,28,29,[146][147][148]150 …”
Section: Population Managementmentioning
confidence: 99%
“…When a surgical candidate is evaluated for gonadectomy, a veterinarian must consider age, body weight, and existing medical conditions that may increase the risk of anesthetic or surgical complications. 150 Potential complications of soft tissue surgery and anesthesia include hemorrhage, hypothermia, pain, wound inflammation, delayed wound healing, dehiscence, and death. 29,[150][151][152][153][154] Studies 28,152,153 based on veterinary students performing OHE and castration have found complication rates of 20% to 30%, but the most common complications were considered minor problems, and the rate of occurrence was thought to be influenced by the experience of the person performing the surgery.…”
Section: Anesthetic and Surgical Complicationsmentioning
confidence: 99%
See 2 more Smart Citations